Foreign Direct Investment (FDI) in Bangladesh: Prospects and Challenges and Its Impact on Economy - Islam, K. M. Anwarul (Asian Business Review, 2014)
This research will try to examine the FDI plays a dominant role in the economy of Bangladesh through accelerating Gross Domestic Product (GDP), export and domestic investment followed by overall economic growth. So it is vital for a developing country like Bangladesh to carry out effective measures in protecting the prospective foreign investors so that they can get a congenial atmosphere to invest their capital. They should feel that their role in the business arena of Bangladesh is respectfully valued. In this connection, friendly regulations, simplifying regulatory practices, investment incentives and removal of inefficient bureaucratic procedures should be ensured.